Electricity reforms and its impact on groundwater use: evidence from India - Mukherji, Aditi; Shah, Tushaar; Verma, S. (2010)
Minimizing the negative impacts of groundwater over-exploitation, while preserving the benefits from such intensive use has emerged as the key natural resources management challenge in South Asia. Direct regulation of groundwater is not a feasible option in the region given over 20 million pumps and the huge transactions costs involved. In this context, indirect mechanism, such as regulation of electricity supply and changes in electricity pricing and subsidies can provide an effective tool for governing groundwater. This chapter documents two such cases of electricity reforms that have had profound impact on groundwater use in Indian states of Gujarat and West Bengal.